IN-SERVICE TEACHERS' THEORETICAL ORIENTATIONS AND CLASSROOM PRACTICES: ANALYSIS OF ESPOUSED BELIEFS AND PERCEIVED PRACTICES - Komo, Teshome Tola (African Journal of Education and Practice, 2020)
Purpose: The purpose of this study was to identify the theoretical orientations that influence teaching practices, and the relationships between beliefs and practices of in-service teacher trainees drawn from different parts of Ethiopia who were attending summer training program in different academic departments of the Addis Ababa University. Methodology: Participants of summer in-service program (N=276) were randomly selected from four subject areas and made to complete a self-report questionnaire designed for this purpose. The questionnaire had 40 Likert Scale type items rated over 5 points so as to collect data on beliefs and practices relating to planning, teaching and assessment behaviors of the surveyed teachers. Findings: The Findings indicated that in most of the cases the beliefs and practices of the surveyed teachers aligned with constructivist reform which the Ethiopian Ministry of Education expects all teachers to implement. Congruence between espoused beliefs and perceived practices were noted with evidence of low relationship between the two. The findings have contributions to raising teachers' tacit knowledge of teaching craft. Insights for educational administrators and areas of focus for future research were also identified.